WORK STRESS, MOTIVATION, FACILITIES, AND TRAINING AS FACTORS AFFECTING EMPLOYEE PERFORMANCE AT KARANGANYAR PRIMARY TAX SERVICE OFFICE - Sutanto, Nugroho Priyo; Titisari, Kartika Hendra; Pawenang, Supawi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Employees are an important asset in the organization. Humans are the driving force and determining the running of an organization, good human resources will produce good performance. The performance of the Tax Office can be assessed by how much the tax target is able to be achieved by all elements of existing human resources. The tax target that has increased every year requires employees to improve their performance. The purpose of this research is test and analyze the effect of stress, motivation, facility, and training on employee performance.The sample in this study were 122 employees at the Karanganyar Primary Tax Office. The data analysis technique used multiple linear regression analysis. The conclusion in this study is an effect of stress, motivation, facilities, and training on the employees performance. Keywords: stress, motivation, facility, training, employee performance